1992
DOI: 10.1002/art.1780350314
|View full text |Cite
|
Sign up to set email alerts
|

Basic calcium phosphate crystals stimulate cell proliferation and collagenase message accumulation in cultured adult articular chondrocytes

Abstract: Objective. To investigate BCP (basic calcium phosphate) crystal-stimulated mitogenesis and collagenase gene transcription in primary cultures of porcine chondrocytes.Methods. The role of protein kinases in BCP crystal4imulated DNA synthesis was investigated using thymidine incorporation, kinase inhibitors, and protein kinase C (PKC) assays. Northern blot analysis was used to determine the levels of collagenase c-fos and c-jun message.Results. BCP crystals stimulated chondrocyte proliferation in a PKC-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
2
24
1
1
Order By: Relevance
“…This postulate is supported in a study by Mitchell et al (6) who found that BCP crystal-induced mitogenesis in Balb/c/3T3 fibroblasts was inhibited when PKC was down-regulated using the tumor-promoting phorbol ester, 12-O-tetradecanoyl-phorbol 13-acetate (TPA), an analogue of diacylglycerol. Another index of PKC activation is translocation of the enzyme from the cytosolic compartment to the membrane compartment of the cell, and we have shown increased membrane-associated PKC activity in porcine chondrocytes treated with BCP crystals (10). These data suggest that the mitogenic response to BCP crystals involves activation of PKC.…”
supporting
confidence: 53%
“…This postulate is supported in a study by Mitchell et al (6) who found that BCP crystal-induced mitogenesis in Balb/c/3T3 fibroblasts was inhibited when PKC was down-regulated using the tumor-promoting phorbol ester, 12-O-tetradecanoyl-phorbol 13-acetate (TPA), an analogue of diacylglycerol. Another index of PKC activation is translocation of the enzyme from the cytosolic compartment to the membrane compartment of the cell, and we have shown increased membrane-associated PKC activity in porcine chondrocytes treated with BCP crystals (10). These data suggest that the mitogenic response to BCP crystals involves activation of PKC.…”
supporting
confidence: 53%
“…Chondrocytes were enzymatically released from cartilage tissue as previously described (18), and plated at high density (4 ϫ 10 5 cells/cm 2 ) in Dulbecco's Modified Eagle's medium (DMEM) with 10% fetal calf serum and 1% penicillinstreptomycin-fungizone (PSF). These conditions maintain the differentiated chondrocyte phenotype (19). Experiments were completed within 3 days of plating.…”
Section: Methodsmentioning
confidence: 99%
“…The BCP crystal-induced PKC activity is blocked by co-treatment of crystal-stimulated cells with the PKC inhibitors, staurosporine and bisindolylmaleimide I (25). Furthermore, an increase in PKC activity associated with the membrane fraction is seen following BCP crystal stimulation of chondrocytes (26). Down-regulation of PKC activity by chronic treatment with the phorbol ester, 12-O-tetradecanoyl-phorbol 13-acetate, an analog of DAG, blocks crystal-induced c-fos and c-myc expressions and mitogenesis in Balb/c 3T3 cells (7) whereas co-treatment with the PKC inhibitor, staurosporine, blocks BCP-induced c-fos expression and mitogenesis in HF (25), indicating that PKC activity is essential for these crystalinduced effects to occur.…”
mentioning
confidence: 88%
“…Because PKC is known to be physiologically active only in the membrane-associated state and translocation of the PKC enzyme from the cytosol to the membrane of the cell is used to monitor its intracellular activation (25,26), we determined PKC activity in the membrane fractions of the cells in calcium-and magnesium-free HBSS and compared it with the activity in HBSS containing calcium and magnesium. Using Gö6976 as the specific inhibitor of the calcium-dependent PKC and PMA as the positive control for the PKC activity, we have shown that there was no PKC activity in the absence of calcium and magnesium as seen in Fig.…”
Section: Participation Of a Protein Kinase Pathway In The Bcp Crystalmentioning
confidence: 99%